PENGARUH BRAND IMAGE DAN PHYSICAL EVIDENCE TERHADAP KEPUTUSAN MENGINAP DI HOTEL AMARIS MUARO BUNGO - Dwi Ningsih, Silpia; Abrian, Youmil (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: This research is motivated by what factors influence a person in making a purchasing decision, including brand image and physical evidence. The decision to buy a product or service is largely determined by the assessment of the quality of the product and service. So because of that this study aims to examine how the influence of Brand Image and Physical Evidence on Residents' Decisions at the Amaris Muaro Bungo Hotel. This study used a quantitative approach, with a sampling technique using purposive sampling. The population and sample in this study are guests who have stayed or are currently staying at the Amaris Muaro Bungo Hotel. Data collection techniques using data collection methods using questionnaires and adapted questionnaires in the validity and reliability tests. Data analysis techniques include data description, analysis requirements test through normality test, heteroscedasticity test, and multicollinearity test. In addition, hypothesis testing is carried out by applying multiple linear regression tests. The results of this study indicate that the Brand Image and Physical Evidence variables have a positive and significant influence on management decisions at Amaris Muaro Bungo Hotel. More specifically, the contribution of the Brand Image (X1) and Physical Evidence (X2) variables to the residential decision (Y) is 64.1%, while 33.9% is influenced by other variables.Keywords: Brand Image, Physical Evidence, Stay Decision.